2022
DOI: 10.1042/ns20210004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the M1 muscarinic acetylcholine receptor in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) remains a major cause of morbidity and mortality worldwide, and despite extensive research, only a few drugs are available for management of the disease. One strategy has been to upregulate cholinergic neurotransmission to improve cognitive function, but this approach has dose-limiting adverse effects. To avoid these adverse effects, new drugs that target specific receptor subtypes of the cholinergic system are needed, and the M1 subtype of muscarinic acetylcholine receptor (M1-mAChR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 142 publications
1
13
0
Order By: Relevance
“…Therefore, it is important to determine the effects of subtype-selective agonists and positive allosteric modulators (PAMs) on intestinal epithelial cell homeostasis and their impact on IBD treatment. In particular, M 1 receptor-selective agonists and PAMs are being actively developed as potential therapeutic agents for schizophrenia and Alzheimer’s disease [ 95 , 96 ]. Exploring the potential of these drugs in the treatment of IBD is an interesting challenge.…”
Section: Machrs As a Potential Therapeutic Target For Ibdmentioning
confidence: 99%
“…Therefore, it is important to determine the effects of subtype-selective agonists and positive allosteric modulators (PAMs) on intestinal epithelial cell homeostasis and their impact on IBD treatment. In particular, M 1 receptor-selective agonists and PAMs are being actively developed as potential therapeutic agents for schizophrenia and Alzheimer’s disease [ 95 , 96 ]. Exploring the potential of these drugs in the treatment of IBD is an interesting challenge.…”
Section: Machrs As a Potential Therapeutic Target For Ibdmentioning
confidence: 99%
“…Acetylcholine (ACh) is one of the important neurotransmitters that play a crucial role in AD pathology and is involved in various biological processes such as attention, learning, memory, stress response, wakefulness and sleep, and sensory information. Earlier reports indicate that selective activation of muscarinic acetyl choline receptor (mAChR) M1 and M3 but not M2 and M4 enhances αAPPs and diminishes the total Aβ formation. Inline, first, cholinesterase inhibitors were tested against AD, and tacrine was the first drug approved for senile AD but soon was withdrawn, due to severe side effects …”
Section: Cholinergic Hypothesismentioning
confidence: 99%
“…Nonetheless, the slow kinetics of [ 18 F]nifzetidine (79) necessitated a prolonged imaging time of greater than 3 h for quantitative PET studies. 195 Further optimization led to the development of 3-(2-(S)-3,4dehydropyrrolinylmethoxy)-5-(3′-[ 18 F]fluoropropyl)pyridine ([ 18 F]nifrolene (80)), which has a binding affinity for α4β2-nAChRs similar to that of 2-[ 18 F]FA (67). 196 In vivo rhesus monkey PET studies of [ 18 F]nifrolene revealed the highest binding in the thalamus followed by regions of the lateral cingulated and temporal cortex and least binding in the cerebellum.…”
Section: Pet Tracers Targeting Nicotinic Acetylcholine Receptors (Nac...mentioning
confidence: 99%